Pemanfaatan Lahan Pekarangan dengan Penanaman Teknik Hidroponik dan Aquaponik sebagai Kulkas Hidup - Husain, Fahrisal; Liswahyuni, Andi Liswahyuni; Nursaifullah, Nursaifullah; Tampubolon, Irianty Tampubolon (ADPERTISI, 2024)
Mattiro Deceng Village is an agricultural area with the majority of rainfed rice fields which have the potential to dry out in the dry season. Community residents often lack fresh water, which can threaten food security. The aim of the socialization activity on the use of hydroponic plants is to increase public understanding about planting techniques without soil which are simply made. It is hoped that these efforts will prevent the risk of stunting in children under five as a result of lack of nutritional intake. The method of this activity is lecture and question and answer. Before the lecture there was a pretest and afterward a posttest was held. Participants in this activity are people who have direct contact with the prevalence of stunting in Mattiro Deceng Village. The results of this activity show an increase in knowledge based on post-counseling practice. Therefore, it is recommended to carry out community service activities in other areas so that the reduction in stunting levels can be realized immediately.